The Analysis of Land Suitability for Sustainable Settlement Development in Kabupaten Manokwari, Provinsi Papua Barat - Ibal, La; Madaul, Rahful Ahmad; Sraun, Randy Stenly (Jurnal Geografika (Geografi Lingkungan Lahan Basah), 2024)
The imbalance between population growth and residential land use by the Spatial Plan and land characteristics has given rise to various problems in Kabupaten Manokwari, including changes in land use and environmental degradation. This study analyzes land suitability as a basis for sustainable settlement development in Kabupaten Manokwari. The research method uses weighting analysis, LCU (Land Capability Unit) overlay, and settlement carrying capacity analysis. The results of the study indicate that (a) Based on the land capability analysis, land development in Kabupaten Manokwari that can be used as a settlement development area is class d and e because it has a flat topography contour and can be developed with a maximum land cover of 70% of the area with an area of 103,053.42 Ha and 44,736.64 Ha respectively; (b) The land carrying capacity of the settlement development area in Kabupaten Manokwari is 3,662.02 Ha; and (c) Sustainable settlement development in Kabupaten Manokwari based on physical components that the direction of raw water utilization in Kabupaten Manokwari is very good with an area of 147,790.06 ha, this shows that for Kabupaten Manokwari there are no obstacles in the utilization of raw water because it has water sources that can be utilized as raw water sources. These findings provide strategic recommendations for the development of residential areas by considering environmental and socio-economic sustainability aspects and supporting the achievement of SDGs goals, especially related to the availability of clean water and sanitation.